Nuclear Weapons Law Where Are We Now? - Boothby, William H. (Social Sciences, 2021)
This book explains in non-technical terms the law applying to the threat or use of nuclear weapons before and during an armed conflict. The rules and implications for nuclear command and control are explained, which will be relevant for politicians, lawyers, military commanders, policy staff, academics and post-graduate students. This book is also available as open access.